Sistem Informasi Pembelajaran Kriptografi Menggunakan Metoda Gost - Sufajar Butsianto (Teknik Informatika, Universitas Pelita Bangsa, 2018)
There are various ways people do to get data and information, although by stealing and then changing the content of the information. In this research, an application is made using cryptographic techniques that can be used to secure information sent via e-mail. The algorithm used is the GOST algorithm (Gosudarstvennyi Standard). The GOST algorithm is a 64-bit symmetric block cipher algorithm which is known to be quite safe because it has 32 rounds in the encryption and decryption process. The programming language used is PHP. In this application the encryption and decryption keys are set by the system, this is done so that key information cannot be easily identified by unauthorized parties. Based on the implementation and testing of the program, it can be concluded that this application is easy to use, messages sent and received through this application are safe because they have gone through the encryption process first. Keywords - Cryptography, E-mail, GOST Algorithm.